2016
DOI: 10.1080/13691058.2016.1183045
|View full text |Cite
|
Sign up to set email alerts
|

What role can gender-transformative programming for men play in increasing men’s HIV testing and engagement in HIV care and treatment in South Africa?

Abstract: Men are less likely than women to test for HIV and engage in HIV care and treatment. We conducted in-depth interviews with men participating in One Man Can (OMC) – a rights-based gender equality and health program intervention conducted in rural Limpopo and Eastern Cape, South Africa – to explore masculinity-related barriers to HIV testing/care/treatment and how participation in OMC impacted these. Men who participated in OMC reported an increased capability to overcome masculinity-related barriers to testing/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 52 publications
7
72
0
Order By: Relevance
“…These types of interventions—often described as ‘gender transformative’—have rarely been applied specifically to increasing HIV testing in Africa, but some recent studies suggest it may be a promising approach. Researchers in South Africa conducted a qualitative evaluation of One Man Can to determine whether it has any impact on men’s HIV testing behaviors even though the program focuses specifically on changing gender norms and does not specifically target a change in HIV testing behaviors [54]. They found that many men reported greater willingness to test for HIV after participating in One Man Can because One Man Can changed their views about gender equity and gender norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of interventions—often described as ‘gender transformative’—have rarely been applied specifically to increasing HIV testing in Africa, but some recent studies suggest it may be a promising approach. Researchers in South Africa conducted a qualitative evaluation of One Man Can to determine whether it has any impact on men’s HIV testing behaviors even though the program focuses specifically on changing gender norms and does not specifically target a change in HIV testing behaviors [54]. They found that many men reported greater willingness to test for HIV after participating in One Man Can because One Man Can changed their views about gender equity and gender norms.…”
Section: Discussionmentioning
confidence: 99%
“…Gender norms related to masculinity may play a critical role in men’s relatively low HIV testing rates [10, 11]. Gender norms are “those qualities of femaleness and maleness that develop as a result of socialization rather than biological predisposition” (p. 146) [12].…”
Section: Introductionmentioning
confidence: 99%
“…One Man Can, Program H) are typically time and resource intensive and involve many workshops and sessions with participants (G. Barker et al, 2004; Paul J Fleming et al, 2016). In contrast, CHARM was relatively brief: it only included three sessions, each of which was relatively brief.…”
Section: Discussionmentioning
confidence: 99%
“…CHARM is a relatively brief intervention compared to other gender-transformative interventions that have been evaluated (G. Barker, Nascimento, Segundo, & Pulerwitz, 2004; Paul J Fleming, Colvin, Peacock, & Dworkin, 2016; Jewkes et al, 2008). Brief interventions are particularly attractive because it can be difficult to engage men in time-intensive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Third, given the link between HIV testing and misogynistic attitudes, gender-transformative interventions may be particularly useful 5557 . Gender-transformative interventions aim to democratize the relationship between men and women and have been shown effective at reducing men’s sexual risk behaviors and violence behaviors 56 and one recent study demonstrated that it may be effective at increasing men’s uptake of HIV testing 58 .…”
Section: Discussionmentioning
confidence: 99%